Physical activity and its association with body mass index among 10-15 years school children in Kalaburagi city, Karnataka, India - Hussain, Mubeen; Tenglikar, Pallavi V.; Nigudgi, S. R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Childhood obesity is a major public health problem, causing a significant morbidity and mortality. The objective of the present study was to identify certain associated risk factors for the prevalence of overweight and obesity among 10-15 years school children. Methods: The present study was carried out in 1,642 school children aged between 10 to 15 years in Kalaburagi city of Karnataka. A predesigned and pretested questionnaire proforma was administered to each child to collect data on their physical activity level, T.V watching, duration of sleep, availability of playground etc. Parameters of height and weight were measured and recorded following completion of the questionnaire. Results: The prevalence of overweight and obesity were more in those students who did not have accessibility of playground in-front of their houses (15.25% and 8.47%) and in those students travelling by Bus (23.16% and 10.17%) and least in those students who reaches their school by walking (8.52% and 3.85%). The prevalence of both overweight and obesity were more in those students who did not participated in any of the outdoor sports (28.52% and 28.52%), who watched Television for more than 7 hours in a week (14.25% and 8.73%) and in those students who slept for less than 6 hours a day (8.75%). Conclusions: Prevalence of overweight and obesity were high among the school children and need to be addressed by primary and secondary methods of prevention.